PEMANFAATAN TEKNOLOGI INFORMASI DALAM PEMBELAJARAN DAN PENELITIAN BAHASA DAN SASTRA - I Wayan Nitayadnya (Balai Bahasa Sulawesi Tengah, 2014)
The progress of technology of the information, bring the new way of-not only formal and nonformal, but also make the language and literature research easier to be done. The advantaging of technology and information in learning and researching should be introduced and developed. For doing this, it needs to increase the ability of teacher/lecturer/instructor/researcher in developing the media of learning, media of socialization, and media of research which is based on the technology ofinformation.